Pesticides in aquatic environments and their removal by adsorption methods. (August 2020) - Mojiri, Amin; Zhou, John L.; Robinson, Brett; Ohashi, Akiyoshi; Ozaki, Noriatsu; Kindaichi, Tomonori; Farraji, Hossein; Vakili, Mohammadtaghi
Abstract: Although pesticides are widely used in agriculture, industry and households, they pose a risk to human health and ecosystems. Based on target organisms, the main types of pesticides are herbicides, insecticides and fungicides, of which herbicides accounted for 46% of the total pesticide usage worldwide. The movement of pesticides into water bodies occurs through run-off, spray drift, leaching, and sub-surface drainage, all of which have negative impacts on aquatic environments and humans. We sought to define the critical factors affecting the fluxes of contaminants into receiving waters. We also aimed to specify the feasibility of using sorbents to remove pesticides from waterways. In Karun River in Iran (1.21 × 10 5  ng/L), pesticide concentrations are above regulatory limits. The concentration of pesticides in fish can reach 26.1 × 10 3  μg/kg, specifically methoxychlor herbicide in Perca fluviatilis in Lithuania. During the last years, research has focused on elimination of organic pollutants, such as pesticides, from aqueous solution. Pesticide adsorption onto low-cost materials can effectively remediate contaminated waters. In particular, nanoparticle adsorbents and carbon-based adsorbents exhibit high performance (nearly 100%) in removing pesticides from water bodies. Graphical abstract: Image 1 Highlights: Pesticides concentrations in water varied widely from 6.8 to 121222 ng/L. A high concentration of Endosulfan was detected in Rohu Fish in India. Carbon-based adsorbents and nano-adsorbents could remove up to 100% pesticides. Mostly organic desorbents have been used for regeneration of adsorbents.